IDENTIFIKASI PATAHAN MIKRO PENYEBAB GEMPA BUMI TARAKAN 21 DESEMBER 2015 - Sriyanto, Sesar Prabu Dwi; Ifantyana, Indri (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
During this time, Borneo island is claimed to be the only island area in Indonesia that relatively safe from earthquake hazard. However, on December 21, 2015 at 01:47:37 am, a big earthquake (Mw 6.1) with a depth of 16 km happened in the Tarakan region. The earthquake shaking was felt by people on 5 MMI intensity scale. In this study, the identification of patterns of micro fracture that triggering Tarakan earthquakes is using the data of earth’s gravitational field, distribution of the earthquake epicenter and focal mechanism of the earthquake. The earth’s gravitational field data is get from the Topex satellite that filtered to obtain residual anomaly with SVD method (Second Vertical Derivative) using Elkins matrix operator. The results of the analysis of Tarakan earthquake parameters in the form of Global CMT focal mechanism and the aftershocks distribution from BMKG database also taken into account in the determination of fracture patterns. From the combination of three types of data we conclude that micro fracture that triggering Tarakan earthquakes on December 21, 2015 is located in the eastern island of Tarakan with moves towards the north-south fault and the type of fracture oblique (the dominance of horizontal fault) as the continuity of Palukoro fault Keywords: micro fracture, earthâ€™s gravitational field, epicenter distribution, focal mechanism..